The topology of the federal funds market - Morten L. Bech; Enghin Atalay (Federal Reserve Bank of New York, 2008)
The recent turmoil in global financial markets underscores the importance of the federal funds market as a means of distributing liquidity throughout the financial system and a tool for implementing monetary policy. In this paper, we explore the network topology of the federal funds market. We find that the network is sparse, exhibits the small-world phenomenon, and is disassortative. In addition, reciprocity loans track the federal funds rate, and centrality measures are useful predictors of the interest rate of a loan.
Keywords: E40; E58; E59; G10; 330; Federal funds; network; topology; interbank; money markets